Dark extinction: the problem of unknown historical extinctions - Boehm, Mannfred M. A. (Biol Lett, 2021)
The extinction of species before they are discovered and named (dark extinction, DE) is widely inferred as a significant part of species loss in the ‘pre-taxonomic’ period (approx. 1500–1800 CE) and, to some extent, in the ‘taxonomic period’ (approx. 1800–present) as well. The discovery of oceanic islands and other pristine habitats by European navigators and the consequent introduction of destructive mammals, such as rats and goats, started a process of anthropogenic extinction. Much ecosystem change happened before systematic scientific recording, so has led to DE. Statistical methods are available to robustly estimate DE in the ‘taxonomic period’. For the ‘pre-taxonomic period’, simple extrapolation can be used. The application of these techniques to world birds, for example, suggests that approximately 56 DEs occurred in the ‘taxonomic period’ (1800–present) and approximately 180 in the ‘pre-taxonomic period’ (1500–1800). Targeting collection activities in extinction hotspots, to make sure organisms are represented in collections before their extinction, is one way of reducing the number of extinct species without a physical record (providing that collection efforts do not themselves contribute to species extinction).